PENGARUH PENGGUNAAN MEDIA CARD SORT AYAT TERHADAP MOTIVASI MEMBACA AL-QUR’AN PADA PEMBELAJARAN AL-QUR’AN HADIST DI MI NU JATIREJO PEMALANG: THE INFLUENCE OF USE OF VERSE SORT CARD MEDIA ON MOTIVATION TO READ THE QUR'AN IN LEARNING THE AL-QUR'AN HADIST AT MI NU JATIREJO PEMALANG - Apriana, Rizki Vina; Rif'iyati, Dian Rif'iyati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The initial aim of this research was to explain how MI NU Jatirejo Pemalang studied Al-Qur'an Hadith using card sort verse media. Second, what inspired MI NU Jatirejo Pemalang students to read the Koran when studying Al-Qur'an Hadith. Third, what is the influence of card sort verse media on students' motivation to read the Al-Qur'an when learning Al-Qur'an Hadith at MI NU Jatirejo Pemalang. This kind of research is quantitative research. The population of all class II MI NU Jatirejo Pemalang students is 30 people. This type of research is field research or is called field research if the researcher goes directly to the field to be researched. This research uses experimental methodology. Data collection methods in this research are observation, initial and final tests, interviews. This data analysis technique uses a paired sample t test with the help of the SPSS version 26 program. The results of this research show that: First, after using the card sort media, the achievement of motivation to read the Al-Qur'an for class II students at MI NU Jatirejo Pemalang showed an increase in the average gain (g) value of 0.65 with the criteria for increasing learning outcomes in the medium category. second, there is a significant influence on reading motivation, as evidenced by the results of the pretest and posttest, it is known that the sample data is 30 students. The students' average Pretest and Posttest scores were 59.43 and 86, namely a difference of 26.57 and an increase of 44.71%. The student's maximum score, which was originally only 70, rose to 97 after receiving learning using card sort media. Third, the results of the pre-test and post-test normality tests obtained a statistical value of 0.118 in the pre-test value with a significance value of 0.200. Meanwhile, the post-test value obtained a statistical value of 0.114 with a significance value of 0.200. It can be concluded that the Kolmogorov Smirnova test is > 0.05, so it can be concluded that the data is normally distributed. The results of the t test show t calculated 52.198 and dk=n-1 = 30-1=29, an error level of 5% is obtained t table (0.05), (29)= 2.045. So t count is 52.198 > t table 2.045, so Ho is rejected and Ha is accepted, which means there is an influence of the use of card sort verse media on reading motivation in learning Al-Qur'an Hadith at MI NU Jatirejo Pemalang.